Calcium Ions Stimulate the Hyperphosphorylation of Tau by Activating Microsomal Prostaglandin E Synthase 1 - Cao, Long-Long; Guan, Pei-Pei; Liang, Yun-Yue; Huang, Xue-Shi; Wang, Pu (Frontiers in Aging Neuroscience, 2019)
Alzheimer’s disease (AD) is reportedly associated with the accumulation of calcium ions (Ca2+), and this accumulation is responsible for the phosphorylation of tau. Although several lines of evidence demonstrate the above phenomenon, the inherent mechanisms remain unknown. Using APP/PS1 Tg mice and neuroblastoma (N)2a cells as in vivo and in vitro experimental models, we observed that Ca2+ stimulated the phosphorylation of tau by activating microsomal PGE synthase 1 (mPGES1) in a prostaglandin (PG) E2-dependent EP receptor-activating manner. Specifically, the highly accumulated Ca2+ stimulated the expression of mPGES1 and the synthesis of PGE2. Treatment with the inhibitor of Ca2+ transporter, NMDAR, attenuated the expression of mPGES1 and the production of PGE2 were attenuated in S(+)-ketamine-treated APP/PS1 Tg mice. Elevated levels of PGE2 were responsible for the hyperphosphorylation of tau in an EP-1-, EP-2- and EP-3-dependent but not EP4-dependent cyclin-dependent kinase (Cdk) 5-activating manner. Reciprocally, the knockdown of the expression of mPGES1 ameliorated the expected cognitive decline by inhibiting the phosphorylation of tau in APP/PS1 Tg mice. Moreover, CDK5 was found to be located downstream of EP1-3 to regulate the phosphorylation of tau though the cleavage of p35 to p25. Finally, the phosphorylation of tau by Ca2+ contributed to the cognitive decline of APP/PS1 Tg mice.